Investor Activity in Chinese Financial Institutions: A Precursor to Economic Sustainability - Rob Kim Marjerison (MDPI AG, 2021)
One requirement for sustainable economic development is established, trusted, and utilized financial institutions to facilitate investment. The rapid development of financial markets in China, combined with the recency and magnitude of middle-class wealth, has resulted in a rapidly changing investment landscape, as well as changes in people’s investing activities. The extent to which economic growth is sustainable will depend, at least in part, on how financial institutions are perceived, as well as the extent to which they are utilized. The objective of this study was to examine the investment behaviors of individual investors as a way to ascertain the perceived level of trust and stability in the relatively recently developed financial institutions. The influence of market information acquisition on asset allocation and value investment in China was analyzed. This study used secondary data from a China securities corporation from previous research. The analyses utilized the general decision-making style test to assess respondents’ decision-making models and quantitative research methodology culminating in the use of correlation analysis. The results indicated that the acquisition of market information had a positive correlation with the number of assets and investment portfolios. Practical implications and suggestions for future research are provided. The results may be of interest to individual and institutional investors in China, as well as those with an interest in current trends in market information acquisition, asset allocation, and value investment in China.